Occupational Therapy in the Urgent and Emergency Hospital: A Case Report (Global Journal of Human-Social Science, 2023)
To discuss the main aspects of the therapeutic-occupational process of a young polytraumatized patient during his hospitalization and to reflect on the clinical reasoning of occupational therapists under the theoretical framework of the Dynamic Occupational Therapy Method. This is a case report of a victim of multiple trauma. A review of the clinical evolution of the team was performed, followed by the description of occupational therapy visits and analysis of the therapeutic process. The subject who suffers a sudden illness has his daily life interrupted by the need for immediate and generally prolonged hospitalization. Dynamic occupational therapy aims to promote the construction of a new routine through its techniques centered on the triadic relationship. This relationship was discussed in three categories: communication, carrying out activities, and addressing palliative care. Urgent and emergency hospitals are fields in growing expansion for occupational therapy, however the performance of this professional in this context is still a little explored subject in Brazil and in the world.
Keywords: occupational therapy; emergency hospital service; spinal cord injury